2015
DOI: 10.1111/ajt.13053
|View full text |Cite
|
Sign up to set email alerts
|

Cervicovaginal HPV Infection in Female Renal Transplant Recipients: An Observational, Self-Sampling Based, Cohort Study

Abstract: Immunosuppressive treatment of organ transplant recipients is associated with an increase in the occurrence of human papillomavirus (HPV) related anogenital (pre)malignancies. This cohort study investigated the genotype-specific prevalence of HPV infections in a large cohort of female renal transplant recipients (RTRs). Participants self-collected a cervicovaginal sample for detection and genotyping of HPV. Besides, they completed a questionnaire regarding sociodemographic variables, medical data and sexual be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
36
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 33 publications
9
36
0
1
Order By: Relevance
“…Reports in HIV+ patients [66], in older women [67] and in transplant [68] are in keeping with this hypothesis. In this latter population having less at-risk sexual behaviours, increased HPV infections and high-grade lesions rates were recently reported [68], differently from previous studies. Therefore, even in the absence of clinically evident lesions and of novel infections, undetected persistence and reactivation of past HR HPV infections would represent an additional risk in immune suppressed women.…”
Section: Hpv-associated Cervical Cancersupporting
confidence: 65%
See 1 more Smart Citation
“…Reports in HIV+ patients [66], in older women [67] and in transplant [68] are in keeping with this hypothesis. In this latter population having less at-risk sexual behaviours, increased HPV infections and high-grade lesions rates were recently reported [68], differently from previous studies. Therefore, even in the absence of clinically evident lesions and of novel infections, undetected persistence and reactivation of past HR HPV infections would represent an additional risk in immune suppressed women.…”
Section: Hpv-associated Cervical Cancersupporting
confidence: 65%
“…Given the ability of HPV DNA to persist long-term in the absence of disease, mucosal immune dysfunction may cause latent HPV reactivation at local sites, despite patient general immune reconstitution [64,65]. Reports in HIV+ patients [66], in older women [67] and in transplant [68] are in keeping with this hypothesis. In this latter population having less at-risk sexual behaviours, increased HPV infections and high-grade lesions rates were recently reported [68], differently from previous studies.…”
Section: Hpv-associated Cervical Cancermentioning
confidence: 87%
“…Lack of baseline antibody levels for some patients is also a limitation; however, a very low prevalence of prevaccination HPV exposure to HPV genotypes 6, 11, 16, and 18 was observed in those patients with baseline data. It is also important to note that patients with transplants who have responded to the quadrivalent HPV vaccine may continue to have higher risk of HPV-related morbidity because of complications from HPV strains not included in the vaccine (35) and b-HPVs (36).…”
Section: Discussionmentioning
confidence: 99%
“…Several large, population‐based registry studies have found that RTRs have an increased risk of HPV‐associated anogenital cancers compared to the general population . It has been hypothesized that the immunosuppressive treatments received by RTRs decrease their ability to clear newly acquired HPV infections and/or increase their risk of reactivation of latent HPV infections . In accordance with this hypothesis, an Australian registry study found that the risk of HPV‐related cancers in RTRs was higher during periods of functioning graft than during periods of dialysis where immunosuppressive treatment is withdrawn or substantially reduced …”
Section: Introductionmentioning
confidence: 97%